HUBUNGAN PENDUGAAN CADANGAN KARBON PADA TEGAKAN JATI MENGGUNAKAN PENGINDERAAN JAUH DAN PENGUKURAN LAPANGAN - Izzuddin Al Qassam; Cahyo Prayogo (Jurnal Tanah dan Sumberdaya Lahan, 2018)
This study was conducted to find out the potential of Landsat 8 OLI / TIRS image to estimate carbon stock and the leverage from image recording scene to its result from estimated carbon stock afterward. This research was conducted at KHDTK Cemoro-Modang. Retrieval and data processing conducted from January to April 2017. There were various data taken during field observation such as diameter at breast height (DBH) in each plot sample, the sample plot represents the Age Class (KU) of teak (Tectona Grandis L) with KU 1, KU2, KU3, KU4, KU5, and KU6. The study used a single channel band of Near Infrared (NIR / Band 5), Shortwave Infrared (SWIR / Band 6 and 7 from Landsat 8 OLI / TIRS and also some vegetation indexes which are Normalized Difference Vegetation Index (NDVI), Simple Ratio (SR), Transformed Difference Vegetation Index (TDVI), Perpendicular Vegetation Index (PVI), Soil Adjusted Vegetation Index (SAVI), Optimized Soil Adjusted Vegetation Index (OSAVI), Visible Atmospherically Resistant Index (VARI) and Green Normalized Difference Vegetation Index (GNDVI). The results of this study showed that Landsat 8 OLI / TIRS image data could be use to estimated carbon stock in landscape of teak stand (Tectona Grandis L), with the model of the best equation is TDVI vegetation index. The equation of the regression test is Y = -3590,557 x + 4033,062 where Y is the carbon value and x is the spectral value of TDVI